Postcolonial Con-Texts : Writing Back to the Canon. - Thieme, John (Literature, culture, and identity., 2002)
In recent years works such as Jean Rhys''s Wide Sargasso Sea, J.M. Coetzee''s Foe and Peter Carey''s Jack Maggs, which ''write back'' to classic English texts, have attracted considerable attention as offering a paradigm for the relationship between post-colonial writing and the ''canon''. Thieme''s study provides a broad overview of such writing, focusing both on responses to texts that have frequently been associated with the colonial project or the construction of ''race'' (The Tempest, Robinson Crusoe, Heart of Darkness and Othello) and texts where the interaction between culture and imper.